Perilaku Cuci Tangan Pakai Sabun terhadap Kejadian Diare pada Balita di Wilayah Kerja Puskesmas Bambu - Ladacing, Nurul Ainun; Ganing, Abdul; Adiningsih, Ridhayani; Ahmad, Haeranah (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Mamuju, 2023)
In 2013, the World Health Organization (WHO) recorded 1.7 billion cases of diarrhea occurring annually with a mortality rate in children under 5 years of 760,000. The aim of this research is to determine the description of CTPS behavior regarding the incidence of diarrhea in toddlers in the Bambu Community Health Center Working Area. This type of research is descriptive research. The research results showed that the knowledge of mothers of toddlers regarding washing hands with soap was mostly good, namely 60.3% and respondents who had less knowledge were 30.7% of respondents. Most of the attitudes of mothers of toddlers regarding washing hands with soap are good, 81.2%, while respondents who have poor attitudes are 18.8%. The actions of mothers of toddlers regarding washing hands with soap mostly have low personal hygiene actions, namely 49.5% and respondents who have good actions. by 50.5%. The conclusion of this research is that the hand washing behavior with soap of mothers of toddlers is mostly good.